2018
DOI: 10.1126/scitranslmed.aat7108
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mutant huntingtin and neurofilament proteins as potential markers in Huntington’s disease

Abstract: Huntington's disease (HD) is a genetic progressive neurodegenerative disorder, caused by a mutation in the gene, for which there is currently no cure. The identification of sensitive indicators of disease progression and therapeutic outcome could help the development of effective strategies for treating HD. We assessed mutant huntingtin (mHTT) and neurofilament light (NfL) protein concentrations in cerebrospinal fluid (CSF) and blood in parallel with clinical evaluation and magnetic resonance imaging in preman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
199
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 165 publications
(218 citation statements)
references
References 55 publications
19
199
0
Order By: Relevance
“…We conducted a prospective cross‐sectional pilot study named “Phase1‐HD” involving participants enrolled simultaneously in the Enroll‐HD study (CHDI Foundation, ) an international multicentre, prospective registry, and in the HD‐CSF study (Byrne, Rodrigues, Johnson, De Vita, et al., ; Byrne, Rodrigues, Johnson, Wijeratne, et al., ), a single‐centre prospective cohort based at the UCL Huntington's Disease Centre, London, UK.…”
Section: Methodsmentioning
confidence: 99%
“…We conducted a prospective cross‐sectional pilot study named “Phase1‐HD” involving participants enrolled simultaneously in the Enroll‐HD study (CHDI Foundation, ) an international multicentre, prospective registry, and in the HD‐CSF study (Byrne, Rodrigues, Johnson, De Vita, et al., ; Byrne, Rodrigues, Johnson, Wijeratne, et al., ), a single‐centre prospective cohort based at the UCL Huntington's Disease Centre, London, UK.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, this study provided decisive preclinical evidence for the concept of "huntingtin holidays" as the basic principle of a disease-modifying strategy for HD patients [24]. Sensitive and standardized immunoassays, which allow the quantification of mutated htt protein in cerebrospinal fluid [25,26], have become available as biomarkers [27].…”
Section: The Scientific Basis For Gene Expression Modification In Hd;mentioning
confidence: 95%
“…In HD, biomarkers have the potential role of assessing therapeutic efficacy, and most recently NF has been tested in both CSF and plasma [35,36,130,131] ( Table 1). A recent study investigated the correlation between mutant huntingtin (mHTT) and CSF and plasma NF-L levels in HD patients, revealing NF-L to be a clinically stronger marker than mHTT, even within the study's limitations [33]. ELISA showed that NF-L levels in CSF of HD patients were significantly higher than those in matched controls [36], while plasma levels of NF-H, using ELISA, excluded this NF subunit as a potential biomarker [130].…”
Section: Huntington's Diseasementioning
confidence: 99%